The impact of fun in the workplace In achieving internal marketing (Applied research) - ABDULZAHRA, ALI HUSSEIN (Journal of Economics and Administrative Sciences, 2021)
The research aims to study the impact of the dimensions of fun in the workplace in achieving internal marketing And knowing the type of relationships That link the dimensions of fun in the workplace With each other, None of the researchers mentioned (to the researcher's knowledge) the link between fun in the workplace and internal marketing From this point of view the main objective is determined, which is to study the effect of fun in the workplace in internal marketing, The research was conducted at Al Salam Public Company for Communications and Information Technology The research community was represented by (308) employees of the aforementioned company , Where a random sample was selected that included (116) employees representing (37.6%) of the total community, The questionnaire was the main tool in collecting data and information As it was distributed randomly to company employees  through assistance of human resources Manager with a view Data processing Many statistical methods were used most notably, standard deviation ,SMA ,Pearson Correlation Coefficient And structural equations model, The most prominent results of the research The existence of a significant correlation and positive relationship between fun in the workplace and internal marketing for the employees of the General Salam Company, also Fun in the workplace have significant and positive effect in the internal marketing of the employees of the aforementioned company , The current research is considered a general review of the concept of fun in the workplace And its impact on achieving internal marketing